Faktor Kesulitan Literasi dan Numerasi dalam Kurikulum Merdeka Belajar - Edy Saputra; Lola Mandasari; Novidayanti M.; Loso Judijanto; Jitu Halomoan Lumbantoruan (Jurnal Pendidikan dan Pengajaran, 2024)
PISA 2018 was released from 78 countries; Indonesia was ranked 70th; only 25% could read, and 24% could count. The research aims to analyze the factors of literacy and numeracy difficulties in the independent learning curriculum. The method used is a mixed method. The subjects were 130 middle school students. Data collection techniques used surveys, observations and interviews. The survey was conducted by distributing instruments to 130 people via Google on a 1-5 point Likert scale. Data was also obtained during randomly selected observations and interviews. The survey analysis technique used SPSS 26, which formed a bar chart. The interview results were analyzed by presenting the data and collecting it, then reducing it, coding it in tables, and verifying the interview with a survey. The results and findings show that 48.63% assess that the Basic Class is difficult to implement, 67.67% assess that the School Culture indicators are not optimal, and 78.54% assess that the Community Base has minimal implementation. The results of observations and interviews also intersect with survey results. According to the third source, indicators of success in literacy and numeracy in schools still need to be fully implemented and meet qualification expectations. In conclusion, minimal implementation of the third indicator impacts students' weak literacy and numeracy skills. This research implies that assignments or projects designed by teachers for students help and train students to improve their literacy and numeracy.